Chapter Studiare la Resistenza con le fonti orali - Contini, Giovanni (Public History of Education. Teorie, esperienze, strumenti, 2022)
Practise in oral interview for recording experiences nurtured during Resistance was early as it was carried on firstly by Silvio Micheli. However, neither Micheli or the Historical Institutes for Resistance studies have been privileged military topics over the other ones. Resistance indeed did not resolve itself only on a military basis. Afterwards, historical research dealt with partisans' daily lives: it showed the human dimension of Resistance as well as difficulties met by partisans, who were politically immature as they were grown during Fascism. Among this new kind of research, the contribute will deal with historical witnesses such as Calegari and Bermani. The pair indeed was characterised by two different way of behaviour.